Systematic review of the role of angiopoietin-1 and angiopoietin-2 in Plasmodium species infections: biomarkers or therapeutic targets?. (December 2016) - Jong, Gerdie; Slager, Jasper; Verbon, Annelies; Hellemond, Jaap; Genderen, Perry
Abstract Background Levels of both angiopoietin-1 (Ang-1) and angiopoietin-2 (Ang-2) correlate with malaria disease severity and are proposed as biomarkers and possible therapeutic targets. To establish their role in malaria, a systematic review was performed of the literature on Ang-1 and Ang-2 with regard to their potential as biomarkers in malaria and discuss their possible place in adjuvant treatment regimens. Methods Ten electronic databases were systematically searched to identify studies investigating Ang-1 and Ang-2 in human and murine malaria in both clinical and experimental settings. Information about the predictive value of Ang-1 and Ang-2 for disease severity and their regulatory changes in interventional studies were extracted. Results Some 579 studies were screened; 26 were included for analysis. In all five studies that determined Ang-1 levels and in all 11 studies that determined Ang-2 in different disease severity states in falciparum malaria, a decline in Ang-1 and an increase of Ang-2 levels was associated with increasing disease severity. All nine studies that determined angiopoietin levels inPlasmodium falciparum patients to study their ability as biomarkers could distinguish between multiple disease severity states; the more the disease severity states differed, the better they could be distinguished. Five studies differentiating malaria survivors from non-survivors with Ang-2 as marker found an AUROC in a range of 0.71–0.83, which performed as well or better than lactate. Prophylactic administration of FTY720, rosiglitazone or inhalation of nitric oxide (NO) during malaria disease in mice resulted in an increase in Ang-1, a decrease in Ang-2 and an increased survival. For rosiglitazone, a decrease in Ang-2/Ang-1 ratio was observed after post-infection treatment in mice and humans with malaria, but for inhalation of NO, an effect on Ang-1 and survival was only observed in mice. Conclusion Both Ang-1 and Ang-2 levels correlate with and can distinguish between malaria disease severity states within the group of malaria-infected patients. However, distinct comparisons of disease severity states were made in distinct studies and not all distinctions made had clinical relevance. Changes in levels of Ang-1 and Ang-2 might also reflect treatment effectiveness and are promising therapeutic targets as part of multi-targeted therapy.